Inovasi Pertunjukan Teater Tradisional Ludruk Di Wilayah Budaya Arek - Autar Abdillah (Institut Seni Indonesia Denpasar, 2009)
Ludruk is one of traditional theatre type in East Java. Jombang Regency was considered become origin place of Ludruk. Then it was spreading wide to Surabaya and generally Arek culture area. This spreading related to the Surabaya position as the big city and trade centre. Moordati stated that “... Surabaya has the own characteristic as the modern harbor city, the biggest both trade and industry through XIX century (Freek Colombijn, dkk (ed), 2005: 302). Surabaya can not compared by any other harbor cities such as Calcutta, Rangoon, Singapore, Bangkok, Hongkong and Shanghai (Howard Dick, 2000: xvii; Moordiati, 2005: 302). Surabaya and Jombang is the base of Arek culture development, except Malang, Mojokerto, Gresik, Kediri, Sidoarjo, and part of Blitar. Along with development of Surabaya city become the trade centre, many theatre groups came here, both from around the cities and Europe. The existence of “Realism” theatre from China and Arab by way of trade mission, and from Dutch and Europe in general through colonial, to establish the development of theatre particularly in Surabaya and East Java in general.